EFL TEACHERS' PERCEPTIONS TOWARDS TEACHER CERTIFICATION PROGRAM - Jamaluddin, - (2009)
The certification program for teachers becomes an actual issue in Indonesia educational system. In this program, the government issues a policy for teachers to increase their competences. In this regard, this study aims to find out what EFL teachers' knowledge about Teacher Certification Program (TCP), what EFL teacher's perception towards TCP, and what EFL teachers' efforts to face TCP. Descriptive research design was used in this study. The data were gained from questionnaire and interview in which 22 EFL teachers involved as respondents. They were chosen by using proportional sampling. This study arrived at three main points as findings. First, although most of respondents state that TCP have been already socialized, yet the obtained data from questionnaires show that majority of respondents do not know that personal competence is assessed in TCP. Again, majority of the respondents also do not know that teachers' personal competence is assessed by headmaster and principal. Second, it is found that all respondents agree that four teacher's competences which involve pedagogical, professional, social, and personal competence should be assessed in TCP. Besides, EFL teachers also agree that teacher certification program will enhance teachers' quality either in portfolio assessment process or in teacher training and education. Related to the process of TCP, the respondents agree that it can be carried out through portfolio assessment, but they add that attending teacher training and education or Pendidikan dan Latihan Profesi Guru (PLPG) is better than taking portfolio assessment. Moreover, majority of the respondents agree that EFL teachers' language skills and language aspects should be also assessed in TCP. Third, it is found that most of the respondents attend seminar and workshop activities to face TCP; only did a small number of them conduct other activities such as developing module and teaching aids, writing article, and conducting classroom action research. Based on these findings, it is suggested to the government to constantly socialize TCP. Then, it is obvious that the mastery of language skills and language aspects constitute the characteristics of professional English teacher. Therefore, it is suggested to the government to make policy to enable assessors whose background is English together with principal and/ or supervisor to assess the teachers in the classroom and/or to allow teachers to submit a CD-ROM containing teaching practice in the classroom. Moreover, it is also suggested to the government to train the teachers to develop their professionalism such as how to develop teaching module and teaching aids, and how to conduct classroom action research.